EVALUASI PENGGUNAAN OBAT ANTI HIPERTENSI TERHADAP PASIEN DI KLINIK TELAGA MEDIKA GUBUG - Kadamsih, Kadamsih; Endang Setyowati; Ulviani Yulia Husna (Yayasan Nusantara Hasana Berdikari, 2025)
Hypertension is a condition of blood pressure that is higher than normal, which can damage vital organs such as the heart, blood vessels, and kidneys. If left untreated, this condition increases the risk of heart attack, stroke, kidney failure, and death. The effectiveness of antihypertensive drugs is determined by their ability to lower blood pressure, generally 7–13 mmHg systole and 4–8 mmHg diastole to achieve blood pressure targets. This study aims to determine the rationality of anti-hypertension which is assessed in terms of the right dosage, indications, patients, and drugs at Telaga Medika Gubug Clinic. This study is a type of observational research (non-experimental) with a descriptive research design using the retrospective cohort method. The approach was carried out retrospectively with a research time of June 1, 2025 The research location was carried out at the Telaga Medika Gubug Clinic, with a total sampling of 155 respondents according to the inclusion and exclusion criteria. For data analysis using frequency distribution. Based on the results of the research on the characteristics of hypertension patients at Telaga Medika Gubug Clinic, the majority age frequency was 51-60 years, namely 81 respondents (52.3%), the gender of the respondent was mostly female, 110 respondents (71.0%), the education of the majority of respondents was high school, namely 54 respondents (34.8%) and the majority of respondents were farmers, 60 respondents (38.7%), the pattern of use of amlodipin as the most antihypertensive drugs (46.36%) and metformin as the most comorbidities (45.97%). All patients are right, namely the right indication, the right patient, and the right dose, but the accuracy of the drug is only 76.8%. The use of antihypertensive drugs at Telaga Medika Gubug Clinic was declared rational, for the accuracy of indications, patients, and dosages while for the accuracy of drugs was only 76.8%.